2015
DOI: 10.1080/2162402x.2015.1036211
|View full text |Cite
|
Sign up to set email alerts
|

Poor survival in glioblastoma patients is associated with early signs of immunosenescence in the CD4 T-cell compartment after surgery

Abstract: $These authors share senior authorship.Keywords: cytomegalovirus, glioblastoma, immunosenescence, survival, T cells Abbreviations: GBM, glioblastoma multiforme; HCMV, human cytomegalovirus; PBMC, peripheral blood mononuclear cell; Valcyte, valganciclovir; WBC, white blood cell countPatients with glioblastoma multiforme (GBM) are immunosuppressed and have a broad range of immunological defects in both innate and adaptive immune responses. GBMs are frequently infected with human cytomegalovirus (HCMV), a virus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…Unexpectedly, the senescence marker KLRG1 was markedly reduced and only presented by a fraction of T cells in the tumor compartment, while CD57 showed an inverse expression pattern, with reduced prevalence in CD8 þ TILs. In one of the first studies providing evidence of alterations in T-cell activation in GBM, Fornara and colleagues (43), demonstrated that a high prevalence of CD4 þ CD57 þ T cells in the blood of patients with GBM correlated with immunosenescence and decreased survival. Extending this work, we observed that CD57 was primarily expressed on CD4 þ TILs, while being reduced on CD8 þ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, the senescence marker KLRG1 was markedly reduced and only presented by a fraction of T cells in the tumor compartment, while CD57 showed an inverse expression pattern, with reduced prevalence in CD8 þ TILs. In one of the first studies providing evidence of alterations in T-cell activation in GBM, Fornara and colleagues (43), demonstrated that a high prevalence of CD4 þ CD57 þ T cells in the blood of patients with GBM correlated with immunosenescence and decreased survival. Extending this work, we observed that CD57 was primarily expressed on CD4 þ TILs, while being reduced on CD8 þ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CMV‐specific CD57 + CD4 + T cells may also represent a mature cellular subset capable of up‐regulating surface CD107a expression (a degranulation marker), although their ability to lyse virus‐infected cells may be compromised due to reduced intracellular content of cytotoxic granules . These findings suggest that markers of immunosenescence in the CD4 + compartment are likely to be associated with poor survival in patients with CMV‐positive GBM and may reflect CMV activity in transformed tissue . However, other reports examining tumour‐infiltrating lymphocytes and in PBMC from patients with cancer show that ‘exhausted’ T cells, e.g.…”
Section: Cmv‐specific Memory Inflation Shapes Global and Anti‐tumour mentioning
confidence: 97%
“…These T cells were unable to produce multiple cytokines and displayed limited cytolytic function . Patients with GBM exhibited a lower frequency of CD3 + T cells compared to healthy individuals but had significantly higher numbers of CD4 + CD28 − T cells before, and after 3 and 12 weeks after surgery in addition to increased levels of CD4 + CD57 + and CD4 + CD57 + CD28 + T cells at all time‐points measured . These T‐cell subsets have been associated with both immunosenescence and CMV infection, as CD57 expression increases with age and in patients with cancer .…”
Section: Cmv‐specific Memory Inflation Shapes Global and Anti‐tumour mentioning
confidence: 99%
See 2 more Smart Citations